2014
DOI: 10.3109/10715762.2014.945079
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial-targeted antioxidant MitoQ ameliorates metabolic syndrome features in obesogenic diet-fed rats better than Apocynin or Allopurinol

Abstract: The prevalence of metabolic syndrome (MetS) components including obesity, dyslipidemia, insulin resistance (IR), and hepatic steatosis is rapidly increasing in wealthy societies. It is accepted that inflammation/oxidative stress are involved in the initiation/evolution of the MetS features. The present work was designed to evaluate the effects of three major cellular ROS production systems on obesity, glucose tolerance, and hepatic steatosis development and on oxidative stress onset. To do so, 40 young male Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 59 publications
5
53
0
Order By: Relevance
“…We were surprised that although our mitoQ treated, HF-fed mice gained less weight than did control HF mice, no difference was seen in hepatic triglyceride or total fat content. However, while this manuscript was in revision, a report appeared describing the effect of mitoQ on features of the metabolic syndrome in HF-fed rats (Feillet-Coudray et al, 2014). Consistent with our observations, these rats gained less weight than controls but also exhibited no change in liver fat content.…”
Section: Discussionsupporting
confidence: 84%
“…We were surprised that although our mitoQ treated, HF-fed mice gained less weight than did control HF mice, no difference was seen in hepatic triglyceride or total fat content. However, while this manuscript was in revision, a report appeared describing the effect of mitoQ on features of the metabolic syndrome in HF-fed rats (Feillet-Coudray et al, 2014). Consistent with our observations, these rats gained less weight than controls but also exhibited no change in liver fat content.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, the results strongly suggested that Mito-Q decreased the levels of protein nitration and HIF-1α stabilization, possibly through suppressing the production of ROS/ RNS. These beneficial results suggest that some synthetic antioxidants are far more effective than the untargeted natural antioxidants in neutralizing elevated nitroxidative stress and metabolic syndrome features, as reported (Feillet-Coudray et al, 2014). Because of the recent clinical testing, we expect to see approval of some of these antioxidants in treating oxidative stress-mediated various forms of liver disease.…”
Section: Translational Research Opportunitiesmentioning
confidence: 68%
“…Further, altered Mitochondrial dynamic and trafficking are also targeted by MitoQ AD and MetS [140,141] Oryzanols, Tocopherols and Tocotrienols…”
Section: Methazolamide (Mtz)mentioning
confidence: 98%